Inspædia: changing the landscape of cultural reflection and influence through user experience design - Maldonado, Paulo (2018)
This article presents and encourages use of Inspædia, the online platform for inspiring collaborative and interactive intelligence. Inspædia’s launch will take place in Los Angeles and will have the 8th AHFE as its backdrop. GET INSPIRED is the provocative and motivational call to action that appears when inspædiers (collaborative visual storytellers) access the online platform at www.inspaedia.com. This is the possible future that inspædiers, when using the platform, feed with new content, new relationships between content, collections of favorite things and navigation trails, helping to collaboratively generate (individual and collective) inspiration, as well as enriching new knowledge by proactively contributing to “BEING innovation”.